Angiokeratoma Circumscriptum - Gupta Sunil k; Aggarwal Kamal; Goel Sanjeev (Wolters Kluwer Medknow Publications, 1998)
A case of Angiokeratoma circumscriptum in a 13 year old female child is reported with swelling over right knee and presence of verrucous plaques on the same studded with papulonodular lesions since birth.